Nanofiltration membranes and their preparation methods, filtration components, and water treatment devices

CN122665495APending Publication Date: 2026-09-01XIAMEN BAILIN WATER PURIFICATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611003367.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

然而,传统的纳滤膜普遍存在膜通量较低、运行压力较高以及膜污染倾向明显等问题

Benefits of technology

[0047] Compared with traditional technologies, the technical advantages of the present application's technical solution include:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

This invention discloses a nanofiltration membrane and its preparation method, filtration component, and water treatment device. The nanofiltration membrane comprises a base membrane and a functional layer disposed on at least one surface of the base membrane. The functional layer is formed by interfacial polymerization of raw materials containing a first component and a second component. The first component comprises a mixture of silk nanofibers and amine compounds containing active hydrogen groups, with a mass ratio of silk nanofibers to the amine compounds containing active hydrogen groups of 1:(0.25-8). The second component comprises an acyl halide compound. This application achieves the preparation of an integrated functional layer by blending silk nanofibers and amine compounds containing active hydrogen groups in a specific ratio in the same phase and then performing interfacial polymerization. This results in a nanofiltration membrane with high flux, high ion rejection rate, and good antifouling effect, which can be widely used in the field of water purification systems. The preparation process is simple and easy to implement industrially, showing good application prospects and industrialization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment technology, and in particular to nanofiltration membranes and their preparation methods, filtration components, and water treatment devices. Background Technology

[0002] As residents' living standards improve, their demands for drinking water quality are constantly increasing. Natural water sources and some municipal water supplies typically contain a certain concentration of calcium ions (Ca). 2+ ) and magnesium ions (Mg 2+ Excessive calcium ions (Ca) can increase water hardness, affecting not only the taste of the water but also easily forming scale inside household water-using appliances such as kettles, water dispensers, and coffee makers, thus reducing the lifespan of these devices. Nanofiltration membranes, due to their ability to selectively retain calcium ions (Ca... 2+ ) and magnesium ions (Mg 2+ Nanofiltration membranes, including divalent ions, allow both beneficial minerals and monovalent ions to pass through, making them promising for water softening. However, traditional nanofiltration membranes generally suffer from low membrane flux, high operating pressure, and a significant tendency to foul. For household water purifiers, the high operating pressure often necessitates the use of booster devices, increasing equipment costs and energy consumption, hindering product lightweighting and widespread adoption, and resulting in insufficient resistance to fouling, leading to poor long-term membrane stability and a decline in filtered water quality. Summary of the Invention

[0003] Therefore, it is necessary to provide a nanofiltration membrane with high flux and excellent antifouling ability at a low operating pressure (≤0.2MPa), as well as its preparation method, filtration components, and water treatment device.

[0004] In a first aspect, this application provides a nanofiltration membrane, including a base membrane and a functional layer disposed on at least one surface of the base membrane; the functional layer is formed by interfacial polymerization of raw materials comprising a first component and a second component;

[0005] The first component comprises a mixture of silk fibroin nanofibers and amine compounds containing active hydrogen groups; the mass ratio of the silk fibroin nanofibers to the amine compounds containing active hydrogen groups is 1:(0.25-8).

[0006] The second component includes an acyl halide compound.

[0007] In some embodiments, the amine compound containing an active hydrogen group has at least one of the following characteristics:

[0008] (1) The amine compounds containing active hydrogen groups include at least one of primary amine compounds and secondary amine compounds;

[0009] Optionally, the secondary amine compounds include cyclic secondary amine compounds;

[0010] Further optionally, the cyclic secondary amine compound includes at least one of piperazine and its derivatives;

[0011] (2) The amine compound containing active hydrogen groups contains at least two active hydrogen groups.

[0012] In some embodiments, it has at least one of the following features:

[0013] (1) The mass ratio of the silk nanofiber to the amine compound containing active hydrogen groups is 1:(1-4).

[0014] (2) The molecular structure of the silk fibroin nanofibers contains at least one functional group selected from hydroxyl, carboxyl, amino and amide groups;

[0015] (3) The silk fibroin nanofibers are prepared by degumming and hydrolyzing the raw materials;

[0016] Optionally, the raw material includes at least one of silkworm silk and spider silk;

[0017] (4) The first component also includes additives;

[0018] Optionally, the additive includes at least one of camphor sulfonic acid, sodium camphor sulfonate, sodium phosphate, and disodium hydrogen phosphate;

[0019] Optionally, the mass ratio of the auxiliary agent to the amine compound containing an active hydrogen group is (0.01-2):(0.5-2).

[0020] (5) The acyl halide compound includes acyl chloride compounds;

[0021] Optionally, the acyl chloride compound includes at least one of pyromellitic methyl methacrylate (PMMA), isophthaloyl chloride (IMMA), terephthaloyl chloride (TMR), phthaloyl chloride (ODM), cyanuric chloride (Citril chloride), citrile chloride (CMC), glutaryl chloride (Glutaryl chloride), and fumarate chloride (FMC).

[0022] In some embodiments, the base film includes a substrate and a resin layer disposed on at least one surface of the substrate, the resin layer being located between the substrate and the functional layer;

[0023] Optionally, the material of the resin layer includes at least one of polysulfone, polyacrylonitrile, polyvinylidene fluoride, and cellulose acetate;

[0024] Optionally, the material of the matrix includes at least one of nonwoven fabric, glass fiber, and porous ceramic.

[0025] In some embodiments, the average pore size of the resin layer is 0.03 μm-0.1 μm; and / or, the thickness of the resin layer is 0.123 mm-0.132 mm.

[0026] Secondly, this application also provides a method for preparing the nanofiltration membrane provided in the first aspect, comprising the following steps:

[0027] The first component is mixed with the first solvent to form a first mixture;

[0028] The second component is mixed with the second solvent to form a second mixture;

[0029] The first mixture is brought into first contact with at least one surface of the base film to form a first material;

[0030] The nanofiltration membrane is prepared by bringing the second mixture into a second contact with the surface forming the first material.

[0031] In some embodiments, the mass fraction of the first component in the first mixture is 0.5%-2%; and / or, the mass fraction of the second component in the second mixture is 0.1%-2%.

[0032] In some embodiments, at least one of the following conditions is also met:

[0033] (1) The first solvent includes a hydrophilic solvent;

[0034] Optionally, the hydrophilic solvent includes water;

[0035] (2) The second solvent includes hydrocarbon solvents;

[0036] Optionally, the hydrocarbon solvent includes at least one of n-hexane, cyclohexane, toluene, n-heptane, and isoalkanes;

[0037] (3) The silk fibroin nanofibers are derived from silk fibroin nanofiber dispersions;

[0038] Optionally, the mass content of the silk fibroin nanofibers in the silk fibroin nanofiber dispersion is 0.5%-1%;

[0039] Optionally, the solvent in the silk nanofiber dispersion includes water;

[0040] (4) The methods of first and second contact can be independently impregnated, dip-coated, sprayed, brushed or roller-coated;

[0041] (5) The first contact time is 0.5 min-30 min;

[0042] (6) The second contact time is 0.5 min-20 min;

[0043] (7) After the second contact, the process also includes a step of heat treatment of the intermediate formed by the second contact;

[0044] Optionally, the heat treatment temperature is 40℃-80℃, and the heat treatment time is 0.5 min-30 min.

[0045] Thirdly, this application also provides a filtration assembly, including the nanofiltration membrane provided in the first aspect and a housing containing the nanofiltration membrane.

[0046] Fourthly, this application also provides a water treatment apparatus, wherein the filter housing of the water treatment apparatus includes at least one filter component provided in the first aspect.

[0047] Compared with traditional technologies, the technical advantages of the present application's technical solution include:

[0048] This application provides a nanofiltration membrane, comprising a base membrane and a functional layer disposed on at least one surface of the base membrane. The functional layer is formed by interfacial polymerization of raw materials comprising a first component and a second component. The first component comprises a mixture of silk nanofibers and an amine compound containing active hydrogen groups, with a mass ratio of silk nanofibers to the amine compound containing active hydrogen groups of 1:(0.25-8). The second component comprises an acyl halide compound. This application achieves the preparation of an integrated functional layer by blending silk nanofibers and amine compounds containing active hydrogen groups in a specific ratio within the same phase and performing interfacial polymerization. This integrated preparation process allows the silk nanofibers to be in situ and uniformly embedded within the polyamide functional layer formed by interfacial polymerization, forming an antifouling functional unit. The nanofiltration membrane provided by this application solves the adverse effects of the independent intermediate functional layer on flux, ion retention, and antifouling performance of traditional nanofiltration membranes, and addresses the technical problems of easy fouling and poor stability in traditional nanofiltration membranes. The nanofiltration membrane provided in this application has high flux and stable operation under low water supply pressure conditions. It has a high rejection rate for magnesium ions (Mg²⁺) and calcium ions (Ca²⁺), giving it a significant advantage in the field of water softening. It also has excellent antifouling performance. The nanofiltration membrane provided in this application is particularly suitable for household water purifiers, kitchen direct drinking water machines, countertop drinking water equipment, and point-of-use drinking water purification systems. Furthermore, the preparation process is simple and easy to implement industrially, showing good market application prospects and industrialization value. Detailed Implementation

[0049] To facilitate understanding of the present invention, preferred embodiments are provided below to provide a more complete description of the invention. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to enable a thorough and complete understanding of the disclosure of the present invention.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0051] In this application, "amine compounds containing active hydrogen groups" refers to a class of organic amines whose molecular structure contains at least one hydrogen atom directly bonded to a nitrogen atom. These compounds can act as nucleophiles, undergoing condensation reactions with the active carbonyl groups in acyl halide compounds, and are core aqueous monomers for preparing polyamide functional layers. "Active hydrogen groups" refer to hydrogen atoms directly bonded to a nitrogen atom, such as -NH and / or -NH2, which possess high reactivity in chemical reactions. "Amine compounds" refer to compounds formed when one or more hydrogen atoms in an ammonia (-NH3) molecule are replaced by hydrocarbon groups (such as alkyl, aryl, etc.).

[0052] The "acyl halide compounds" mentioned in this application are compounds with a "-COX" group formed by replacing the hydroxyl group in a carboxylic acid with a halogen atom. They can be classified into acyl fluorides, acyl chlorides, acyl bromides, and acyl iodides. Among them, "halogen" refers to F, Cl, Br, or I.

[0053] Traditional nanofiltration membranes generally suffer from low flux, high operating pressure, and significant fouling tendency. To improve nanofiltration membrane performance, researchers have attempted to introduce nanomaterials for modification. For example, it has been reported that nanomaterials are pre-coated onto a porous substrate to form an independent intermediate layer, and then a nanofiltration membrane is prepared by interfacial polymerization of piperazine (PIP) and trimesoyl chloride (TMC) on the surface of the intermediate layer, which can improve water flux to some extent. However, the pre-formed intermediate layer still resists water molecule transport, making it difficult to achieve a synergistic improvement in high flux, high calcium and magnesium ion rejection rate, and antifouling performance under low-pressure operating conditions. Furthermore, this pre-coating method requires additional spraying and drying steps, making the preparation process complex and unsuitable for low-cost large-scale production.

[0054] Based on this, this application aims to solve the technical problems caused by the independent intermediate layer formed during the nanofiltration membrane preparation process, and to realize a nanofiltration membrane with high throughput, low pressure operation and good antifouling ability.

[0055] In a first aspect, this application provides a nanofiltration membrane, including a base membrane and a functional layer disposed on at least one surface of the base membrane; the functional layer is formed by interfacial polymerization of raw materials comprising a first component and a second component; the first component comprises a mixture of silk nanofibers and an amine compound containing active hydrogen groups; the mass ratio of silk nanofibers to the amine compound containing active hydrogen groups is 1:(0.25-8); the second component comprises an acyl halide compound.

[0056] This application uses a mixture of silk fibroin nanofibers (SNF) and amine compounds containing active hydrogen groups as the first component, which is then interfacially polymerized with a second component containing acyl halide compounds to form a functional layer. By pre-mixing SNF with amine compounds containing active hydrogen groups and then interfacially polymerizing it with the second component containing acyl halide compounds, a functional layer is directly formed on the surface of the base membrane in a one-step process. This technique enhances the hydrophilicity of the membrane and simultaneously enables intermolecular forces such as hydrogen bonding to participate in the construction of the functional layer's microstructure during the interfacial reaction, thereby creating channels conducive to water molecule transport and reducing the adsorption and fouling tendency of calcium, magnesium ions, and organic pollutants on the membrane surface. Compared to traditional nanofiltration membranes, this eliminates the need for a separate intermediate layer, solving the resistance caused by the intermediate layer in traditional nanofiltration membranes. This achieves excellent high-flux operation of the nanofiltration membrane under low pressure while improving its antifouling performance. The preparation process of this application achieves efficient removal and long-term stable operation of calcium and magnesium ions under low pressure conditions, overcoming the shortcomings of traditional nanofiltration membranes such as low flux, poor fouling resistance, and complex processes.

[0057] The term "interfacial polymerization" in this application refers to a polycondensation reaction that occurs at the interface (or on the organic phase side of the interface) between two immiscible solutions containing two different monomers. It is understood that the first and second components of this application are two immiscible solution systems, wherein the first component is an aqueous phase and the second component is an oil phase, and interfacial polymerization is achieved through the aqueous and oil phases.

[0058] In some embodiments, the amine compound containing an active hydrogen group includes at least one of a primary amine compound and a secondary amine compound.

[0059] In some embodiments, the secondary amine compounds include cyclic secondary amine compounds. Exemplarily, cyclic secondary amine compounds include at least one of piperazine (PIP) and its derivatives. As a non-limiting example, derivatives of piperazine include at least one of 2,2-dimethylpiperazine and 2,5-dimethylpiperazine.

[0060] In some embodiments, the amine compound containing an active hydrogen group comprises at least two active hydrogen groups. It is understood that the active hydrogen group includes at least one of a primary amine (-NH2) and a secondary amine (-NH).

[0061] In some embodiments, the molecular structure of silk fibroin nanofibers (SNFs) contains at least one functional group selected from hydroxyl, carboxyl, amino, and amide groups. This application utilizes the hydrophilic functional groups such as hydroxyl, carboxyl, amino, and amide groups on the surface of SNFs to form stable intermolecular interactions with amine compounds containing active hydrogen groups. This forms a durable and stable hydration layer during interfacial polymerization, and moderately adjusts the diffusion rate of amine compounds containing active hydrogen groups to the reaction interface, making the interfacial polymerization reaction more uniform and controllable. The physical interlocking and intermolecular interactions between SNFs and the polyamide network help improve the structural uniformity and density of the functional layer, forming a thinner, defect-free polyamide functional layer. This achieves microstructural control of the functional layer and ensures effective sieving of calcium and magnesium ions. Compared with the traditional method of constructing an intermediate layer using SNFs followed by interfacial polymerization modification, this application organically combines functional nanomaterials with the interfacial polymerization process. This simplifies the preparation process while reducing interlayer interface defects, resulting in a structurally stable nanofiltration separation functional layer with excellent mass transfer performance. It also improves the hydrophilicity of the membrane surface, thereby reducing the deposition and adsorption tendency of organic pollutants on the membrane surface.

[0062] This application constructs an integrated interfacial polymerization system that combines reactive and structural regulation functions by directly blending SNF with amine compounds containing active hydrogen groups, and then participating in an interfacial polymerization reaction with a system containing acyl halide compounds. Through this synergistic regulation mechanism, the constructed functional layer exhibits excellent hydrophilicity, ion selectivity, and antifouling properties, meeting the application requirements of household drinking water softening for low-pressure operation, efficient removal of calcium and magnesium ions, and long-term stable use.

[0063] In some embodiments, the mass ratio of silk nanofibers to amine compounds containing active hydrogen groups is 1:(0.25-8), including but not limited to 1:0.25, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or any combination thereof and values ​​within that range. It is understood that within this raw material ratio range, in the polyamide functional layer structure formed by interfacial polymerization, silk nanofibers can form continuous hydrophilic mass transfer pathways, which is beneficial for reducing water molecule transport resistance and increasing membrane flux. Further, the mass ratio of silk nanofibers to amine compounds containing active hydrogen groups is 1:(1-4).

[0064] In some embodiments, the raw materials for preparing silk nanofibers include at least one of silkworm silk and spider silk. As a non-limiting example, silkworm silk includes at least one of domesticated silkworm silk, tussah silk, castor silk, and wild silkworm silk.

[0065] In some embodiments, the silk fibroin nanofibers are derived from a silk fibroin nanofiber dispersion. As a non-limiting example, the solvent in the silk fibroin nanofiber dispersion includes water.

[0066] In some preferred embodiments, the mass content of silk nanofibers in the silk nanofiber dispersion is 0.5%-1%.

[0067] In some specific embodiments, the preparation steps of the SNF dispersion include: degumming and acid hydrolyzing the raw materials to prepare the first fiber, mixing the first fiber with water to prepare the SNF dispersion.

[0068] The degumming step includes: mixing the raw materials with an alkaline solution and boiling them to obtain coarse fibers, washing and drying the coarse fibers to prepare dried filaments.

[0069] The acid hydrolysis step includes: mixing the degummed dry filaments with acid solution for hydrolysis, washing the hydrolyzed fibers, and preparing the first fiber.

[0070] As a non-limiting example, acid includes sulfuric acid.

[0071] As a non-limiting example, the washing solution is stopped when the pH is 6.5-7.0 at the end of the washing process.

[0072] In this mixture, the mass content of the first fiber in the solution formed by mixing the first fiber with water is 0.5%-1%. It can be understood that the mass content of silk fibroin nanofibers in the silk fibroin nanofiber dispersion is 0.5%-1%.

[0073] In some embodiments, the process of preparing SNF dispersion includes the steps of ultrasonic treatment of the mixture and solid-liquid separation to obtain a clear liquid after the first fiber is mixed with water.

[0074] In some embodiments, the acyl halide compound includes an acyl chloride compound. As a non-limiting example, the acyl chloride compound includes at least one selected from pyromellitic methyl methacrylate (PMMA), isophthaloyl chloride (IMMA), terephthaloyl chloride (TMR), phthaloyl chloride (DMR), cyanuric chloride (CYM), citrate chloride (CIC), glutaryl chloride (Glutaryl chloride), and fumarate chloride (FMA).

[0075] In some embodiments, the base film includes a substrate and a resin layer disposed on at least one surface of the substrate, the resin layer being located between the substrate and the functional layer.

[0076] In some embodiments, the material of the resin layer includes at least one selected from polysulfone, polyacrylonitrile, polyvinylidene fluoride, and cellulose acetate. As a non-limiting example, polysulfone includes polyethersulfone.

[0077] In some embodiments, the matrix material includes at least one of nonwoven fabric, glass fiber, and porous ceramic.

[0078] In some embodiments, the average pore size of the resin layer is 0.03 μm-0.1 μm; further, the average pore size of the resin layer is 0.03 μm-0.06 μm.

[0079] In some embodiments, the average pore size of the substrate is 0.03 μm-20 μm, including but not limited to 0.03 μm, 0.1 μm, 0.25 μm, 0.5 μm, 1 μm, 2.5 μm, 5 μm, 7.5 μm, 10 μm, 15 μm, 20 μm or any of the foregoing ranges and values ​​within that range.

[0080] In some embodiments, the thickness of the resin layer is 0.123 mm-0.132 mm; preferably 0.127 mm-0.130 mm.

[0081] In some preferred embodiments, the method for preparing the base film includes:

[0082] The resin material, solvent and pore-forming agent are mixed and degassed to prepare a casting solution. The casting solution is then applied to the surface of the substrate and treated to form a base film.

[0083] In some preferred embodiments, the treatment includes a phase inversion process. It is understood that the phase inversion process includes placing an intermediate formed after the casting solution is coated onto the surface of the substrate in a coagulation bath (deionized water) for phase inversion. As a non-limiting example, the phase inversion temperature is 30-70°C. As a non-limiting example, the phase inversion time is 4 min.

[0084] In some embodiments, the resin content is 16%-20% by mass percentage of the casting solution, including but not limited to 16%, 17%, 18%, 19%, 20% or any of the foregoing ranges and values ​​within those ranges.

[0085] In some embodiments, the content of the pore-forming agent is 1%-12% by mass percentage of the casting solution, including but not limited to 1%, 2%, 5%, 8%, 10%, 12% or any of the foregoing ranges and values ​​within those ranges.

[0086] In some embodiments, the matrix material includes at least one of nonwoven fabric, glass fiber, and porous ceramic. As a non-limiting example, the nonwoven fabric includes at least one of polyester (PET) nonwoven fabric, polypropylene (PP) nonwoven fabric, and polyethylene (PE) nonwoven fabric.

[0087] In some embodiments, the porogen includes at least one selected from polyethylene glycol, propanol, isopropanol, glycerol, polyvinylpyrrolidone, and polyethylene oxide. As a non-limiting example, the polyethylene glycol has a molecular weight of 400-8000; as a non-limiting example, the polyvinylpyrrolidone includes at least one selected from K30, K60, K70, K80, and K90; as a non-limiting example, the polyethylene oxide has a molecular weight of 40000-1200000.

[0088] In some preferred embodiments, the pore-forming agent comprises polyethylene glycol and polyvinylpyrrolidone (PVP); further, the mass ratio of the polyethylene glycol to the polyvinylpyrrolidone is (3-4):(1-2).

[0089] In some embodiments, the first component further includes an auxiliary agent. As a non-limiting example, the auxiliary agent includes at least one selected from camphor sulfonic acid, sodium camphor sulfonate, sodium phosphate, and disodium hydrogen phosphate. It is understood that the auxiliary agent, as a surfactant, is used to regulate the diffusion behavior of PIP, effectively reducing the activation energy of the reaction and adjusting the interfacial polymerization rate.

[0090] In some preferred embodiments, the mass ratio of the auxiliary agent to the amine compound containing an active hydrogen group is (0.01-2):(0.5-2).

[0091] Secondly, this application also provides a method for preparing the nanofiltration membrane provided in the first aspect, comprising the following steps:

[0092] S1. The first component is mixed with the first solvent to form a first mixture.

[0093] S2. The second component is mixed with the second solvent to form a second mixture.

[0094] S3. The first mixture is brought into first contact with at least one surface of the base film to form a first material.

[0095] S4. The second mixture is brought into a second contact with the surface forming the first material to prepare the nanofiltration membrane.

[0096] In some embodiments, the first contact time is 0.5 min to 30 min; further, the first contact time is 1 min to 15 min.

[0097] In some embodiments, the second contact time is 0.5 min to 20 min; further, the second contact time is 0.5 min to 5 min.

[0098] In some embodiments, the first solvent comprises a hydrophilic solvent. As a non-limiting example, the hydrophilic solvent includes water.

[0099] In some embodiments, the content of the mixture (composed of silk nanofibers and amine compounds containing active hydrogen groups) in the first component is 0.5%-2% based on the mass percentage of the first mixture, including but not limited to 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2% or any of the foregoing ranges and values ​​within those ranges.

[0100] In some embodiments, the second solvent comprises a hydrocarbon solvent. As a non-limiting example, the hydrocarbon solvent includes at least one selected from n-hexane, cyclohexane, toluene, n-heptane, and isoalkanes. The isoalkanes are selected from at least one of ISOPAR G and ISOPAR L.

[0101] In some preferred embodiments, the content of the acyl halide compound in the second component is 0.1%-2% by mass percentage of the second mixture, including but not limited to 0.1%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2% or any of the foregoing ranges and values ​​within those ranges.

[0102] This application constructs an integrated interfacial polymerization system that combines reaction function and structure regulation function by directly blending SNF with an amine compound containing an active hydrogen group in the same aqueous solution system, and then participating in an interfacial polymerization reaction with an oil solution system containing an acyl halide compound.

[0103] In some embodiments, the first and second contacts can be made independently of dipping, immersion coating, spraying, brushing, or roller coating.

[0104] In some embodiments, after the second contact, the process further includes a step of heat-treating the intermediate formed by the second contact.

[0105] In some embodiments, the heat treatment temperature is 40°C-80°C; further, the heat treatment temperature is 50°C-70°C.

[0106] In some embodiments, the heat treatment time is 0.5 min to 30 min; further, the heat treatment time is 1 min to 10 min.

[0107] In some embodiments, after the heat treatment step, the material after heat treatment is further cleaned.

[0108] Thirdly, this application also provides a filtration assembly, including the nanofiltration membrane provided in the first aspect and a housing for accommodating the nanofiltration membrane.

[0109] Fourthly, this application also provides a water treatment apparatus, the filter housing of which includes at least one filter component provided in the first aspect.

[0110] For experimental parameters not specified in the following specific embodiments, please refer to the guidelines given in this application document first, or refer to experimental manuals or other experimental methods known in the art, or refer to the experimental conditions recommended by the manufacturer.

[0111] The raw materials and reagents involved in the following specific embodiments can be obtained commercially or prepared by those skilled in the art using known methods.

[0112] The sources of some of the raw materials and reagents used in this application are as follows:

[0113] The preparation method of silk fibroin nanofiber dispersion is as follows:

[0114] Degumming: Weigh 10 g of silk, cut the raw silk into small pieces and put it into a 0.5 wt% Na2CO3 aqueous solution (500 mL). Stir continuously in boiling water for 30 min, discard the used Na2CO3 solution, and then pour in a new Na2CO3 aqueous solution (500 mL) and heat to boiling again for 30 min. Then rinse the silk fibers with a large amount of deionized water and dry them to obtain dried silk.

[0115] Acid hydrolysis: Soak the dried fibers in a 40 wt% sulfuric acid solution (250 mL) and hydrolyze continuously in a 60℃ water bath for 1 h. Immediately rinse the fibers with a large amount of deionized water 3-5 times until the pH of the washing solution is 6.5-7.0 and then stop rinsing.

[0116] Preparation of silk fibroin fiber dispersion: The cleaned wet fibers were dispersed in deionized water at a concentration of 0.5 wt%-1 wt% for swelling. The swollen dispersion was ultrasonically treated for 40 min, and then centrifuged at 9000 rpm for 20 min using a high-speed centrifuge. The supernatant was carefully aspirated to obtain the silk fibroin nanofiber dispersion.

[0117] Polysulfone resin: Ultrason® S 6010 NAT, purchased from BASF, Germany.

[0118] Polyethersulfone resin: Ultrason® E 6020 NAT, purchased from BASF, Germany.

[0119] Polyacrylonitrile resin: Product number P303199, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0120] Example 1

[0121] This application provides a process for preparing a nanofiltration membrane, the specific steps of which are as follows:

[0122] Preparation of porous ultrafiltration membrane: Polymer resin (polysulfone resin) was dissolved in N,N-dimethylacetamide (DMAc), and porogens (PEG-400, PVP K30) were added. The content of polymer resin in the mixture was 16 wt% and the content of porogen was 5 wt% (4 wt% PEG-400, 1 wt% PVP K30). After stirring and dissolving at 60℃, the mixture was filtered and allowed to stand for degassing for 12 h to obtain a uniform and stable casting solution. The prepared casting solution was then degassed under vacuum for 30 min (-0.098 MPa) and coated onto the surface of one side of the nonwoven fabric. After coating, it was immersed in a coagulation bath (deionized water) at 50°C for phase inversion (the replacement time between solvent and non-solvent was 4 min) to obtain a wet porous ultrafiltration base membrane with a resin layer on the surface of the nonwoven fabric (the average pore size of the ultrafiltration layer was 0.03 μm, the thickness of the nonwoven fabric was about 0.095 mm, and the total thickness of the base membrane was 0.127 mm).

[0123] Preparation of aqueous solution 1: Piperazine and sodium camphor sulfonate were added sequentially to deionized water and dispersed evenly to obtain aqueous solution 1. The content of piperazine in aqueous solution 1 was 1 wt% and the content of sodium camphor sulfonate was 0.1 wt%.

[0124] Preparation of aqueous solution 2: Take 50 mL of 0.5 wt% silk fibroin nanofiber dispersion and mix it with 25 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0125] Preparation of organic phase solution: Dissolve pyromellitic chloride in organic solvent ISOPAR G to prepare 100 mL of organic phase solution containing 0.1 wt% pyromellitic chloride.

[0126] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous phase solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The residual liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 minutes. The porous ultrafiltration base membrane was taken out and placed in an oven for heat treatment at 70°C for 3 minutes. Finally, the membrane was immersed and rinsed in deionized water to obtain a high-flux antifouling nanofiltration membrane.

[0127] Example 2

[0128] This application provides a process for preparing a nanofiltration membrane, the specific steps of which are as follows:

[0129] Preparation of porous ultrafiltration membrane: Polymer resin (polysulfone resin) was dissolved in N,N-dimethylacetamide (DMAc), and porogens (PEG-400, PVP K30) were added. The content of polymer resin in the mixture was 16 wt% and the content of porogen was 5 wt% (4 wt% PEG-400, 1 wt% PVP K30). After stirring and dissolving at 60℃, the mixture was filtered and allowed to stand for degassing for 12 h to obtain a homogeneous and stable casting solution. Subsequently, the prepared casting solution was degassed under vacuum for 30 min (-0.098 MPa) and coated onto one side of a nonwoven fabric. After coating, it was immersed in a coagulation bath (deionized water) at 50℃ for phase inversion for 4 min to obtain a wet porous ultrafiltration membrane with a resin layer on the nonwoven fabric surface (the average pore size of the ultrafiltration layer was 0.03 μm, the thickness of the nonwoven fabric was about 0.095 mm, and the total thickness of the membrane was 0.127 mm).

[0130] Preparation of aqueous solution 1: Piperazine and sodium camphor sulfonate were added sequentially to deionized water and dispersed evenly to obtain aqueous solution 1. The content of piperazine in aqueous solution 1 was 1 wt% and the content of sodium camphor sulfonate was 0.1 wt%.

[0131] Preparation of aqueous solution 2: Take 50 mL of 0.5 wt% silk fibroin nanofiber dispersion and mix it with 50 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0132] Preparation of organic phase solution: Dissolve pyromellitic chloride in organic solvent ISOPAR G to prepare 100 mL of organic phase solution containing 0.1 wt% pyromellitic chloride.

[0133] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous phase solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The residual liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 minutes. The porous ultrafiltration base membrane was taken out and placed in an oven for heat treatment at 70°C for 3 minutes. Finally, the membrane was immersed and rinsed in deionized water to obtain a high-flux antifouling nanofiltration membrane.

[0134] Example 3

[0135] This application provides a process for preparing a nanofiltration membrane, the specific steps of which are as follows:

[0136] Preparation of porous ultrafiltration membrane: Polymer resin (polysulfone resin) was dissolved in N,N-dimethylacetamide (DMAc), and porogens (PEG-400, PVP K30) were added. The content of polymer resin in the mixture was 16 wt% and the content of porogen was 5 wt% (4 wt% PEG-400, 1 wt% PVP K30). After stirring and dissolving at 60℃, the mixture was filtered and allowed to stand for degassing for 12 h to obtain a homogeneous and stable casting solution. Subsequently, the prepared casting solution was degassed under vacuum for 30 min (-0.098 MPa) and coated onto the surface of one side of nonwoven fabric. After coating, it was immersed in a coagulation bath (deionized water) at 50℃ for phase inversion for 4 min to obtain a wet porous ultrafiltration membrane with a resin layer on the surface of the nonwoven fabric (the average pore size of the ultrafiltration layer was 0.03 μm, the thickness of the nonwoven fabric was about 0.095 mm, and the total thickness of the membrane was 0.127 mm).

[0137] Preparation of aqueous solution 1: Piperazine and sodium camphor sulfonate were added sequentially to deionized water and dispersed evenly to obtain aqueous solution 1. The content of piperazine in aqueous solution 1 was 1 wt% and the content of sodium camphor sulfonate was 0.1 wt%.

[0138] Preparation of aqueous solution 2: Take 50 mL of 0.5 wt% silk fibroin nanofiber dispersion and mix it with 100 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0139] Preparation of organic phase solution: Dissolve pyromellitic chloride in organic solvent ISOPAR G to prepare 100 mL of organic phase solution containing 0.1 wt% pyromellitic chloride.

[0140] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous phase solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The residual liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 minutes. The porous ultrafiltration base membrane was taken out and placed in an oven for heat treatment at 70°C for 3 minutes. Finally, the membrane was immersed and rinsed in deionized water to obtain a high-flux antifouling nanofiltration membrane.

[0141] Example 4

[0142] This application provides a process for preparing a nanofiltration membrane, the specific steps of which are as follows:

[0143] Preparation of porous ultrafiltration membrane: Polymer resin (polysulfone resin) was dissolved in N,N-dimethylacetamide (DMAc), and porogens (PEG-400, PVP K30) were added. The content of polymer resin in the mixture was 16 wt% and the content of porogen was 5 wt% (4 wt% PEG-400, 1 wt% PVP K30). After stirring and dissolving at 60℃, the mixture was filtered and allowed to stand for degassing for 12 h to obtain a homogeneous and stable casting solution. Subsequently, the prepared casting solution was degassed under vacuum for 30 min (-0.098 MPa) and coated onto the surface of one side of nonwoven fabric. After coating, it was immersed in a coagulation bath (deionized water) at 50℃ for phase inversion for 4 min to obtain a wet porous ultrafiltration membrane with a resin layer on the surface of the nonwoven fabric (the average pore size of the ultrafiltration layer was 0.03 μm, the thickness of the nonwoven fabric was about 0.095 mm, and the total thickness of the membrane was 0.127 mm).

[0144] Preparation of aqueous solution 1: Piperazine and sodium camphor sulfonate were added sequentially to deionized water and dispersed evenly to obtain aqueous solution 1. The content of piperazine in aqueous solution 1 was 2 wt% and the content of sodium camphor sulfonate was 0.1 wt%.

[0145] Preparation of aqueous solution 2: Take 50 mL of 1 wt% silk fibroin nanofiber dispersion and mix it with 50 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0146] Preparation of organic phase solution: Dissolve pyromellitic chloride in organic solvent ISOPAR G to prepare 100 mL of organic phase solution containing 0.1 wt% pyromellitic chloride.

[0147] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous phase solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The residual liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 minutes. The porous ultrafiltration base membrane was taken out and placed in an oven for heat treatment at 70°C for 3 minutes. Finally, the membrane was immersed and rinsed in deionized water to obtain a high-flux antifouling nanofiltration membrane.

[0148] Example 5

[0149] This application provides a process for preparing a nanofiltration membrane, the specific steps of which are as follows:

[0150] Preparation of porous ultrafiltration membrane: Polymer resin (polyethersulfone resin) was dissolved in N,N-dimethylacetamide (DMAc), and porogens (PEG-1000, PVP K30) were added. The content of polymer resin in the mixture was 16 wt% and the content of porogen was 5 wt% (3 wt% PEG-1000, 2 wt% PVP K30). After stirring and dissolving at 60℃, the mixture was filtered and allowed to stand for degassing for 12 h to obtain a homogeneous and stable casting solution. Subsequently, the prepared casting solution was degassed under vacuum for 30 min (-0.098 MPa) and coated onto the surface of one side of a nonwoven fabric. After coating, it was immersed in a coagulation bath (deionized water) at 50℃ for phase inversion for 4 min to obtain a wet porous ultrafiltration membrane with a resin layer on the surface of the nonwoven fabric (the average pore size of the ultrafiltration layer was 0.06 μm, the thickness of the nonwoven fabric was about 0.095 mm, and the total thickness of the membrane was 0.129 mm).

[0151] Preparation of aqueous solution 1: 2,5-dimethylpiperazine and sodium camphor sulfonate were added sequentially to deionized water and dispersed evenly to obtain aqueous solution 1. The content of 2,5-dimethylpiperazine in aqueous solution 1 was 1 wt% and the content of sodium camphor sulfonate was 0.1 wt%.

[0152] Preparation of aqueous solution 2: Take 50 mL of 1 wt% silk fibroin nanofiber dispersion and mix it with 50 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0153] Preparation of organic phase solution: Dissolve pyromellitic chloride in organic solvent ISOPAR G to prepare 100 mL of organic phase solution containing 0.1 wt% pyromellitic chloride.

[0154] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous phase solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The residual liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 minutes. The porous ultrafiltration base membrane was taken out and placed in an oven for heat treatment at 70°C for 3 minutes. Finally, the membrane was immersed and rinsed in deionized water to obtain a high-flux antifouling nanofiltration membrane.

[0155] Example 6

[0156] This application provides a process for preparing a nanofiltration membrane, the specific steps of which are as follows:

[0157] Preparation of porous ultrafiltration membrane: Polymer resin (polyacrylonitrile resin) was dissolved in N,N-dimethylacetamide (DMAc), and porogens (PEG-1000, PVP K30) were added. The content of polymer resin in the mixture was 16 wt% and the content of porogen was 5 wt% (3 wt% PEG-1000, 2 wt% PVP K30). After stirring and dissolving at 60℃, the mixture was filtered and allowed to stand for degassing for 12 h to obtain a homogeneous and stable casting solution. Subsequently, the prepared casting solution was degassed under vacuum for 30 min (-0.098 MPa) and coated onto the surface of one side of a nonwoven fabric. After coating, it was immersed in a coagulation bath (deionized water) at 50℃ for phase inversion for 4 min to obtain a wet porous ultrafiltration membrane with a resin layer on the surface of the nonwoven fabric (the average pore size of the ultrafiltration layer was 0.04 μm, the thickness of the nonwoven fabric was about 0.095 mm, and the total thickness of the membrane was 0.130 mm).

[0158] Preparation of aqueous solution 1: 2,5-dimethylpiperazine and camphor sulfonic acid were added sequentially to deionized water and dispersed evenly to obtain aqueous solution 1. The content of 2,5-dimethylpiperazine in aqueous solution 1 was 1 wt% and the content of camphor sulfonic acid was 0.1 wt%.

[0159] Preparation of aqueous solution 2: Take 50 mL of 1 wt% silk fibroin nanofiber dispersion and mix it with 50 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0160] Preparation of organic phase solution: Dissolve pyromellitic chloride in organic solvent ISOPAR G to prepare 100 mL of organic phase solution containing 0.1 wt% pyromellitic chloride.

[0161] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous phase solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 min. The residual liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 min. The porous ultrafiltration base membrane was taken out and placed in an oven for heat treatment at 70℃ for 3 min. Finally, the membrane was immersed and rinsed in deionized water to obtain a high-flux antifouling nanofiltration membrane.

[0162] Comparative Example 1

[0163] The difference from Example 1 is that no silk fibroin nanofiber dispersion is added (the preparation of aqueous solution 2 is not carried out), and the aqueous solution 2 is replaced by aqueous solution 1 for dip coating in the nanofiltration membrane preparation step. The other components and preparation methods are the same as in Example 1.

[0164] Comparative Example 2

[0165] The difference from Example 4 is that no silk fibroin nanofiber dispersion is added (the preparation of aqueous solution 2 is not carried out), and aqueous solution 1 is used to replace aqueous solution 2 in the nanofiltration membrane preparation step. The other components and preparation methods are the same as in Example 4.

[0166] Comparative Example 3

[0167] The difference from Example 1 is that the silk fibroin nanofiber dispersion is replaced with an equal amount and concentration of carboxymethyl cellulose nanofiber dispersion, while the other components and preparation methods are the same as in Example 1.

[0168] The preparation method of carboxymethyl cellulose nanofiber dispersion is as follows:

[0169] Preparation of sodium carboxymethyl cellulose (CMC-Na) solution: Accurately weigh 1.0 g of CMC-Na powder and slowly add it to 99 mL of deionized water with stirring. Continue to stir magnetically at room temperature for 4-6 hours until a uniform and transparent solution is formed, thus obtaining a 1.0 wt% CMC-Na stock solution.

[0170] Take the above 1.0 wt% CMC-Na stock solution, dilute it with deionized water to 0.5 wt%, adjust the pH to 6.0, let it stand at room temperature for 24 h, and then sonicate the resulting suspension for 10 min (ultrasonic power of 300 W), and then centrifuge at 8000 rpm for 15 min. Take the supernatant to obtain the carboxymethyl cellulose nanofiber dispersion.

[0171] Comparative Example 4

[0172] The difference from Example 1 is that the silk fibroin nanofiber dispersion is replaced with an equal amount and concentration of sericin protein dispersion, while the other components and preparation methods are the same as in Example 1.

[0173] The preparation method of the sericin protein dispersion is as follows:

[0174] Degumming: Mix silk and water at a ratio of 1g:200ml, boil at 100℃ for 30 minutes to dissolve the sericin from the fibroin and obtain a crude sericin extract.

[0175] Dialysis: The crude sericin extract was placed into a dialysis bag with a molecular weight cutoff (MWCO) of 20,000 Da.

[0176] Purification: Place the dialysis bag in deionized water and dialyze slowly at 4°C for 72 hours with the water changed multiple times during the process to remove small molecule impurities.

[0177] Concentration and drying: The dialyzed sericin solution is rotary evaporated and then freeze-dried to obtain high-purity sericin protein powder;

[0178] Finally, 0.5 g of sericin powder was added to 99.5 mL of deionized water and sonicated to obtain a 0.5 wt% sericin dispersion.

[0179] Comparative Example 5

[0180] The difference from Example 1 lies in the preparation of the aqueous solution and the method of preparing the nanofiltration membrane, as detailed below:

[0181] The preparation of the porous ultrafiltration membrane and aqueous solution 1 is the same as in Example 1.

[0182] Preparation of aqueous solution 2': Take 50 mL of 0.5 wt% silk fibroin nanofiber dispersion and place it in an ice-water bath for ultrasonic dispersion (power 400w) for 30 min to obtain aqueous solution 2'.

[0183] Preparation of nanofiltration membrane: A self-made porous ultrafiltration base membrane was cut to a certain size and placed in a self-made dip-coating fixture. Excess water on the membrane surface was dried, and then aqueous solution 2 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The remaining liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and aqueous solution 1 was poured in to dip and coat the porous ultrafiltration base membrane for 3 minutes. The remaining liquid on the membrane surface was removed by purging with a 0.2 MPa nitrogen gas knife. Then, the porous ultrafiltration base membrane was transferred to another fixture, and an organic phase solution was poured in to dip and coat the porous ultrafiltration base membrane for interfacial polymerization for 0.5 minutes. The porous ultrafiltration base membrane was removed and placed in an oven for heat treatment at 70°C for 3 minutes. Finally, the membrane was immersed and rinsed in deionized water to obtain the nanofiltration membrane.

[0184] Comparative Example 6

[0185] The difference from Example 1 lies in the different mass ratio of silk fibroin nanofibers to piperazine, specifically:

[0186] Preparation of aqueous solution 2: Take 50 mL of 0.5 wt% silk fibroin nanofiber dispersion and mix it with 5 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0187] The remaining components and preparation methods are the same as in Example 1.

[0188] Comparative Example 7

[0189] The difference from Example 1 lies in the different mass ratio of silk fibroin nanofibers to piperazine, specifically:

[0190] Preparation of aqueous solution 2: Take 50 mL of 0.5 wt% silk fibroin nanofiber dispersion and mix it with 250 mL of the above aqueous solution 1. Place it in an ice-water bath and sonicate (power 400w) for 30 min to obtain mixed aqueous solution 2.

[0191] The remaining components and preparation methods are the same as in Example 1.

[0192] Experimental Example 1

[0193] The nanofiltration membranes prepared in the examples and comparative examples were subjected to performance tests. The total thickness of the resin-based membrane portion (non-woven fabric + resin layer) in the nanofiltration membrane structure ranged from 0.127 mm to 0.130 mm. The test methods and indicators are as follows:

[0194] Membrane separation performance: The flux and separation performance of nanofiltration membrane samples were tested using a flat-panel membrane cross-flow filtration performance evaluation device. The test methods for flux and inorganic salt rejection rate are as follows: The operating pressure was set to 0.25 MPa, the pre-pressurization time was 30 min, and then the pressure was adjusted to 0.2 MPa. After stable operation for 30 min, a certain volume of filtrate was taken and the sampling time was recorded. The membrane flux F (L·m) was calculated using formula (1). -2 ·h -1 ·bar -1 The retention rates of the corresponding inorganic salts were calculated using formula (2). All data were the average of three parallel tests under the same conditions. The spiking solution for the flux test was deionized water, and the spiking solutions for the inorganic salt retention rate test were 250 mg / L MgSO4, 250 mg / L CaCl2, and 250 mg / L NaCl solutions.

[0195] (1)

[0196] In equation (1), F is the water flux, L / (m³). 2 (·h·bar); V is the volume of permeate collected within time t, in L; A is the effective membrane area, in m². 2 ; t is the time (h) for collecting volume V of permeate; P is the operating pressure (bar).

[0197] (2)

[0198] In equation (2), R is the retention rate, %; C p The conductivity of the permeate is expressed in μS / cm; Cf The conductivity of the test solution is expressed in μS / cm.

[0199] Membrane antifouling performance test: Using a flat-sheet membrane cross-flow filtration performance evaluation device, with a 250 mg / L magnesium sulfate solution as the initial feed liquid, the initial flux (F0, L / (m)) of the tested examples and the prepared nanofiltration membrane samples was determined. 2 The initial rejection rate (R0, %) and the initial rejection rate (R0, %) are calculated as shown in (3) and (4); with humic acid as the pollution source, the nanofiltration membrane is rinsed with deionized water for 30 min after 48 h of operation, and the flux of magnesium sulfate solution (F1, L / (m)) is tested again. 2 ·h·bar)) and retention rate (R1, %).

[0200] The rate of decrease in flux before and after pollution (%) = (F0-F1) / F0×100% (3)

[0201] The reduction rate of retention rate before and after pollution (%) = (R0-R1) / R0×100% (4)

[0202] Membrane contact angle test: The contact angle of the nanofiltration membrane samples from the examples and preparations was measured using a contact angle goniometer. The volume of the water droplet added during measurement was 5 μL. The sampling points were located at any 5 positions on the sample, and the average value of the contact angle was taken.

[0203] The performance test results of the nanofiltration membranes prepared in the examples and comparative examples are shown in Tables 1 and 2:

[0204] Table 1: Test results of flux, ion rejection and contact angle performance of nanofiltration membranes

[0205]

[0206] Table 2: Test results of antifouling performance of nanofiltration membranes

[0207]

[0208] As shown in Tables 1 and 2, the nanofiltration membrane prepared by blending silk fibroin nanofibers and amine compounds containing active hydrogen groups in the same aqueous solution and then performing integrated interfacial polymerization can achieve a significant increase in flux at a pressure of 0.2 MPa (close to tap water pressure), and also improve the removal efficiency of calcium and magnesium ions. In contrast, the nanofiltration membranes prepared in Comparative Examples 1-7 showed a significant decrease in pure water flux, ion rejection rate, and overall hydrophilicity performance under the same pressure. Specifically, methods such as not adding SNF, forming an SNF membrane layer on the resin membrane first, or using CMC-Na or silk fibroin instead of SNF were difficult to achieve the technical effects of this application. Furthermore, the ratio of SNF to PIP content also significantly affected the overall performance of the nanofiltration membrane after interfacial polymerization. In addition, the water contact angle and antifouling test results of the examples and comparative examples show that the nanofiltration membrane prepared in this application has a smoother surface, stronger hydrophilicity, better antifouling ability, and better long-term operational stability.

[0209] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0210] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A nanofiltration membrane, characterized in that, It includes a base film and a functional layer disposed on at least one surface of the base film; the functional layer is formed by interfacial polymerization of raw materials comprising a first component and a second component; The first component comprises a mixture of silk fibroin nanofibers and amine compounds containing active hydrogen groups; the mass ratio of the silk fibroin nanofibers to the amine compounds containing active hydrogen groups is 1:(0.25-8). The second component includes an acyl halide compound.

2. The nanofiltration membrane according to claim 1, characterized in that, The amine compound containing an active hydrogen group has at least one of the following characteristics: (1) The amine compounds containing active hydrogen groups include at least one of primary amine compounds and secondary amine compounds; Optionally, the secondary amine compounds include cyclic secondary amine compounds; Further optionally, the cyclic secondary amine compound includes at least one of piperazine and its derivatives; (2) The amine compound containing active hydrogen groups contains at least two active hydrogen groups.

3. The nanofiltration membrane according to claim 1, characterized in that, It has at least one of the following characteristics: (1) The mass ratio of the silk nanofiber to the amine compound containing active hydrogen groups is 1:(1-4). (2) The molecular structure of the silk fibroin nanofibers contains at least one functional group selected from hydroxyl, carboxyl, amino and amide groups; (3) The silk fibroin nanofibers are prepared by degumming and hydrolyzing the raw materials; Optionally, the raw material includes at least one of silkworm silk and spider silk; (4) The first component also includes additives; Optionally, the additive includes at least one of camphor sulfonic acid, sodium camphor sulfonate, sodium phosphate, and disodium hydrogen phosphate; Optionally, the mass ratio of the auxiliary agent to the amine compound containing an active hydrogen group is (0.01-2):(0.5-2). (5) The acyl halide compound includes acyl chloride compounds; Optionally, the acyl chloride compound includes at least one of pyromellitic methyl methacrylate (PMMA), isophthaloyl chloride (IMMA), terephthaloyl chloride (TMR), phthaloyl chloride (ODM), cyanuric chloride (Citril chloride), citrile chloride (CMC), glutaryl chloride (Glutaryl chloride), and fumarate chloride (FMC).

4. The nanofiltration membrane according to any one of claims 1 to 3, characterized in that, The base film includes a substrate and a resin layer disposed on at least one surface of the substrate, the resin layer being located between the substrate and the functional layer; Optionally, the material of the resin layer includes at least one of polysulfone, polyacrylonitrile, polyvinylidene fluoride, and cellulose acetate; Optionally, the material of the matrix includes at least one of nonwoven fabric, glass fiber, and porous ceramic.

5. The nanofiltration membrane according to claim 4, characterized in that, The resin layer has an average pore size of 0.03 μm-0.1 μm; and / or the resin layer has a thickness of 0.123 mm-0.132 mm.

6. The method for preparing a nanofiltration membrane according to any one of claims 1 to 5, characterized in that, Includes the following steps: The first component is mixed with the first solvent to form a first mixture; The second component is mixed with the second solvent to form a second mixture; The first mixture is brought into first contact with at least one surface of the base film to form a first material; The nanofiltration membrane is prepared by bringing the second mixture into a second contact with the surface forming the first material.

7. The method for preparing a nanofiltration membrane according to claim 6, characterized in that, The mass fraction of the first component in the first mixture is 0.5%-2%; and / or the mass fraction of the second component in the second mixture is 0.1%-2%.

8. The method for preparing a nanofiltration membrane according to claim 6 or 7, characterized in that, It also meets at least one of the following conditions: (1) The first solvent includes a hydrophilic solvent; Optionally, the hydrophilic solvent includes water; (2) The second solvent includes hydrocarbon solvents; Optionally, the hydrocarbon solvent includes at least one of n-hexane, cyclohexane, toluene, n-heptane, and isoalkanes; (3) The silk fibroin nanofibers are derived from silk fibroin nanofiber dispersions; Optionally, the mass content of the silk fibroin nanofibers in the silk fibroin nanofiber dispersion is 0.5%-1%; Optionally, the solvent in the silk nanofiber dispersion includes water; (4) The methods of first and second contact can be independently impregnated, dip-coated, sprayed, brushed or roller-coated; (5) The first contact time is 0.5 min-30 min; (6) The second contact time is 0.5 min-20 min; (7) After the second contact, the process also includes a step of heat treatment of the intermediate formed by the second contact; Optionally, the heat treatment temperature is 40℃-80℃, and the heat treatment time is 0.5 min-30 min.

9. A filter assembly, characterized in that, It includes the nanofiltration membrane as described in any one of claims 1 to 5 and the housing containing the nanofiltration membrane.

10. A water treatment device, characterized in that, The filter housing of the water treatment device includes at least one filter component as described in claim 9.